Grado de satisfacción con la simulación y prácticas docentes tradicionales en la adquisición de competencias clínicas en reanimación cardiopulmonar en estudiantes de medicina de la universidad técnica particular de Loja. Septiembre 2012-febrero 2013. - Valdez Narváez, Karina del Cisne (2014)
The main objective of this research work is to compare two different methodologies of teaching in students and teachers from medicine, to acquire clinic competences in cardiopulmonary revival through surveys in order to analyze and know what the satisfaction level is. This research work is a descriptive, prospective and comparative model with transversal and quantitative design approach. The results according to the satisfaction level in the Likert scale with a score over 5 were: 2,70/5 (40%)for professors who are little satisfied and 2,71/5 (32,79%) for students who are little satisfied in relation to the teaching traditional practice. The results from workshops about simulation were 4,49/5 ( 57,46%) from the Likert scale for students who were fulfilled and similarly with 4,5/5 (70%) for teachers. From the results of advantages and disadvantages with 83,33% from professors who pointed out their pro for the simulation workshops. Finally, according to the satisfaction level from professors and teachers in relation to the simulation workshops, there is a mayor acceptation for traditional method.